The performance implications of relationship banking during macroeconomic expansion and contraction: a study of Japanese banks' social relationships and overseas expansion - WAN, William P. (Institutional Knowledge at Singapore Management University, 2008)
We propose a social perspective emphasizing the opportunities and constraints of bank-firm relationships to understand the determinants of relationship banks' performance, using Japanese banks to test our theory. Using social exchange and role theories, we found banks that have strong social relationships performed differently during Japan's macroeconomic expansion and contraction cycles. However, our results indicate that social exchange and role relationships are context-specific: banks benefited from internationalization during a domestic macroeconomic expansion as a result of their home-country social relationships, but they were less constrained by the same social relationships in their international operations during a domestic macroeconomic contraction.